Effect of different glucose-lowering therapies on cancer incidence in type 2 diabetes: An observational population-based study. (September 2018) - Vicentini, Massimo; Ballotari, Paola; Giorgi Rossi, Paolo; Venturelli, Francesco; Sacchettini, Claudio; Greci, Marina; Mangone, Lucia; Pezzarossi, Annamaria; Manicardi, Valeria
Highlights: No effect of metformin on all-sites cancer incidence. A possible protective effect for breast, liver and prostate cancer incidence. Our study's time-related bias-free results were consistent with those from RCTs. Abstract: Aim: To assess the effect of metformin on cancer incidence in type 2 diabetes (T2DM), considering possible interactions with other glucose-lowering drugs and diabetes duration. Methods: Study cohort included diabetes patients aged 20–84 on December 2009, still alive and resident in Reggio Emilia province as of December 2011. Drug exposure was assessed for 2009–2011; subjects taking metformin continuously, with or without other hypoglycaemic drugs, were compared to subjects on diet-only therapy. The cohort was followed up from 2012 to 2014 through the cancer registry. Age- and sex-adjusted incidence rate ratios (IRRs) were computed using Poisson regression models for all sites, lung, breast, liver, colorectal, prostate and pancreatic cancer. Results: The cohort includes 17, 026 people with T2DM, 7460 taking metformin. 887 cancers occurred during follow-up, 348 among metformin users. Cancer risk was similar in T2DM patients using metformin and those on diet-only. The risk for prostate (IRR = 0.65; 95%CI:0.36; 1.17), liver (IRR = 0.82; 95%CI:0.36; 1.85) and breast (IRR = 0.77; 95%CI:0.43; 1.40) cancers only was slightly reduced; for lung (IRR = 1.52; 95%CI:0.92; 2.50), pancreas (IRR = 1.51; 95%CI:0.59:3.89) and colon-rectum (IRR = 1.71; 95%CI:0.94; 3.08) the risk was slightly increased. Conclusions: There is no evidence of antitumor effect of metformin. A possible decrease only for breast, liver and prostate cancer, is compatible with random fluctuations.